Kai Althoff - And then leave me to the common swifts = Kai Althoff - Und dann überlaßt mich den Mauerseglern - Naiditch, Dovber; Rothkopf, Constantin (The Museum of Modern Art, 2016)
"Published in conjunction with the exhibition 'Kai Althoff: and then leave me to the common swifts', presented at The Museum of Modern Art, New York, from September 18, 2016, to January 22, 2017"